Contradiction and Conflict : The Popular Church in Nicaragua - Sabia, Debra, 1957- (Book collections on Project MUSE., 1997)
Debra Sabia establishes that, contrary to what has been thought, the popular church was neither homogeneous nor unified and that divergent notions of the popular church exist in Nicaragua. Using the work of Max Weber as a model in developing a theoretical framework for examining the popular church in Nicaragua, Sabia divides the popular church community into four ideal types: the Marxist, the Christian Revolutionary, the Reformist, and the Alienated Christian. Each ideal type is differentiated by its members' general orientation to spiritual and political beliefs and practices. Sabia provides important details about the origins and impact of these divisions, and she is especially sensitive to the groups' and individuals' own perceptions of their particular blend of religion and politics. By examining the impact of the popular church on the revolution and, conversely, the effect that Nicaraguan politics has had on the popular church, the study offers original conclusions for assessing the future viability of the popular church in the counterrevolutionary state.